2006
DOI: 10.1002/bdrb.20074
|View full text |Cite
|
Sign up to set email alerts
|

Embryotoxicity of oral administered chlorothalonil in mice

Abstract: On the basis of the present results chlorothalonil can produce clinical signs of toxicity and fetotoxicity without teratogenic effects at 400 and 600 mg/kg/day dose groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 10 publications
0
6
1
Order By: Relevance
“…Despite the absence of impact on the weight and histology of the kidneys observed in this study, Farag et al (2006) observed increase in the absolute weight of this organ after exposure to 600 mg -1 kg -1 day of chlorothalonil (GD 6-15) in mice. In addition, Wilkinson & Killen (1996) reported that chronic exposure of rodents to chlorothalonil can cause nephrotoxicity and renal tubular hyperplasia.…”
Section: Parametercontrasting
confidence: 87%
See 3 more Smart Citations
“…Despite the absence of impact on the weight and histology of the kidneys observed in this study, Farag et al (2006) observed increase in the absolute weight of this organ after exposure to 600 mg -1 kg -1 day of chlorothalonil (GD 6-15) in mice. In addition, Wilkinson & Killen (1996) reported that chronic exposure of rodents to chlorothalonil can cause nephrotoxicity and renal tubular hyperplasia.…”
Section: Parametercontrasting
confidence: 87%
“…Control CT400 CT800 CT1200 nucleus, suggestive of apoptosis, and area of microvesicular steatosis). In contrast, increase in the absolute weight of liver after exposure to chlorothalonil (600 mg -1 kg -1 day) was observed by Farag et al (2006). Some studies (Paolini et al 1999, Buono et al 2007 indicate that thiophanate-methyl may lead to hepatic morphological alterations, glycogen depletion and hepatocellular apoptosis.…”
Section: Parametermentioning
confidence: 96%
See 2 more Smart Citations
“…Although the treatments produced no mortality, signs of toxicity, such as weakness and reduced activity did occur at the 400 and 600 mg/kg/day dose levels (Farag et al 2006). Also observed at these concentrations was significant embryo lethality and a reduction in live fetuses (Farag et al 2006). According to the US EPA (1999), chlorothalonil is considered to be practically non-toxic to small mammals, based on having a measured rat LD 50 of >10,000 mg/kg.…”
Section: Mammalsmentioning
confidence: 92%